The Role Of Fine Motor Abilities In Reading Components: A Cross-Sectional Study In Children With And Without Dyslexia: Fine motor and reading in Dyslexia - Barghandan, Reza; Dadgar, Hooshang; Raji, Parvin; Maroufizadeh, Saman (Iranian Journal of Child Neurology, 2023)
Objectives This study aimed to investigate the relationship between fine motor skills and reading components and compare the fine motor skills of normal children and children with dyslexia. Materials & Methods In this study, 47 children with dyslexia children and 47 normal children in the first to the third grade of elementary school in the age range of seven to nine years were examined with the Bruininks- Oseretsky Test of Motor Proficiency and NEMA reading test. Data were analyzed using Kolmogorov-Smirnov, Shapiro-Wilk, U Mann-Whitney methods, multiple linear regression, and Spearman correlation coefficient. Results The results showed children with dyslexia were significantly weaker in fine motor skills than normal children (p <0.001). In addition, a relationship existed between the subtest of response speed and reading accuracy in normal children, but it was in normal children. A significant relationship was found between visual-motor control subtests and Upper-limb speed and dexterity with reading accuracy and speed. None of the motor subtests were related to reading comprehension. In children with dyslexia, no association was found between motor subtests and reading components. Conclusion Seemingly, fine motor skills can be used as an essential factor along with other effective factors in improving the reading skills of children with reading disabilities